The Impact of Chronic Kidney Disease on Iron Metabolism and Hemoglobin Parameter in Patients with and without Diabetes Mellitu (Bangladesh Medical Journal, 2025)
Chronic kidney disease (CKD) is one of the most common public health concerns around the world with numerous adverse outcomes such as cardiovascular disease (CVD), end stage renal disease (ESRD) and premature death. The progression of the CKD leads to an increase in the development of hematological alterations, such as low hemoglobin levels and iron deficiency. Diabetes mellitus is the most common cause of CKD, leading to ESRD and therefore, is also the most common cause of renal anemia. The aim of this study was to find out the influence of Iron Metabolism and Hemoglobin parameter among CKD patients with and without diabetes mellitus by determining iron profile and hemoglobin level. This cross-sectional analytical study was carried out in the department of Nephrology, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka over a period of one year July 2022 to June 2023. A total of 100 CKD patients were included in this study as respondents and divided them in to two halves; 50 CKD patients with DM were selected as group- I and other 50 CKD patients without DM as group II. After taking written informed consents, data were taken from patients by using a structured questionnaire. Data was analyzed by Statistical Package for Social Sciences (SPSS), version- 26. In this study serum iron was found significantly lower in group- I (Mean±SD: 6.16±2.36) than group- II (Mean±SD: 12.73±7.36), which was statistically significant. Group- I also represents 56% absolute iron deficiency, 18% functional iron deficiency and 26% normal iron status, Group- II represents 18% absolute iron deficiency, 38% functional iron deficiency and 44% normal iron status respectively. These differences between two groups were statistically significant (p value: